Turmeric: Alternative Therapy Against MDR Staphylococcus aureus, Preservative, Shelf-life the Miced Meat - Yusra M. Baqer Muhsin (College of Pharmacy / Mustansiriyah University, 2013)
Aqeous and alcoholic extract of turmeric (Curcuma longa) were evaluated for its antimicrobial action against the food borne and food spoilage pathogen, Staphylococcus aureus, that resistant concentrations (Minimum inhibition concentration (MIC) and Minimum bactericidal concentration (MBC)) of C.longa against S.aureus were found using MIC and MBC assay,miced meat was taken as the standard sample to test for the turmeric upon MDR S. aureusduring 6 days storage and compared with sodium nitrate.Turmeric extract exhibited anti-MDR S.aureus activity with all concentration-dependent relationship.the alcohol extracts were the most efficient,then aqueous extracts and both of them with high significant differences compared with sodium nitrate(preservative). The value of MIC and MBC of turmeric was 2.5 ml and was the efficient when used in miced meat storage assay for 6 days with high significant differences compared with sodium nitrate.